Implication on Firm Value in Indonesian Banking - Sainada Oktoby Sherly Abdillah; Fitri Yani Jalil (Department of Accounting-Faculty of Economic and Business (FEB), 2022)
The level of investor prosperity is reflected in the stock price. Financial statement ratio analysis is used to determine the value of a company. Because banking is the focal point of the country’s economic activity, it attracts investors. The goal of this research is to look into the impact of profitability, growth opportunity, dividend policy, and firm age on the firm value of Indonesian commercial banks listed on the Indonesia Stock Exchange between 2015 and 2021. Purposive sampling was used in this study, and 59 data points were analyzed using multiple regression analysis. The findings revealed that profitability has a significant impact on firm value. Meanwhile, growth prospects, dividend policy, and firm age have no effect on firm value. Investors are drawn in by the size of the company’s profit. Due to a lack of understanding of the company’s internal and external conditions, bank growth does not always reflect abundant assets. Capital gains are preferred by many investors because they produce quick profits. The vulnerability of a company to new competitors grows with age.